Development of novel alginate lyase cross-linked aggregates for the oral treatment of cystic fibrosis - Islan, German Abel (2014)
Alginate lyase (AL) from Sphingobacterium multivorum is unsuitable for oral delivery because of its rapid inactivation under acidic conditions. The synthesis of a novel crosslinking enzyme aggregate (CLEA) of AL (AL-CLEA) is proposed. AL precipitation with 95% ammonium sulfate and combined with low methoxylated pectin (LMP), showed 100% precipitation yield. Crosslinking with glutaraldehyde reduced the AL-CLEA activity to less than 1%, but addition of bovine serum albumin (BSA) and LMP during AL-CLEA synthesis increased the activity yield to 14.7%. AL-CLEA exposed to simulated gastric conditions (pH 1.2 to 3.0) showed more than 70% retention of enzymatic activity. Moreover, AL-CLEA showed thermal stability at temperatures over 37 °C. Stability against chemical denaturants (ethanol, acetone and propylene glycol) showed that AL-CLEA was 14 times more stable than free AL in all cases. Finally, a 25% viscosity reduction of alginate solution was achieved with AL-CLEA. This is the first report of AL-CLEA synthesis and evaluation.